Evaluation of Different Sterilization Methods on Try-In Preformed Stainless Steel Crowns and Their Consequences: An In Vivo Microbiological Study - Namratha Tharay; G Dhanu; Raghavendra Havale; Kanchan M Tuppadmath; Prem Lata; Santhebachalli Prakasha Shrutha (Journal of South Asian Association of Pediatric Dentistry)
Aim and background: Stainless steel crowns (SSC) in pediatric dentistry are prefabricated; they must be selected and tried, which subjects them to contamination with biological fluids. Therefore, these crowns must be sterilized before reuse. This study aims to evaluate different methods of sterilization of tried-in SSCs in children between the ages of 4 and 10 years. Methods: This is a single-centered, equivalence, randomized in vivo microbiological study with a parallel design and balanced allocation ratio. Based on inclusion criteria, 90 children were included. The tried-in SSCs were incubated for Streptococcus mutans count using suitable culture media. Later, the same tried-in crowns were allotted to six groups of sterilization methods through block randomization. The methods’ efficacy was evaluated in the same way as before sterilization. Further, crazing was analyzed using a stereomicroscope. Results: The mean colony-forming units (CFUs) after the sterilization period were significantly lower (p < 0.001) than before. The crazing grades, when assessed statistically, showed a significant difference between the groups (p < 0.001). Conclusion: Autoclaving can be considered an effective means of sterilizing tried-in SSCs. However, regarding crazing and the time factor, 2% glutaraldehyde may be a better option. Clinical significance: This study helps address the gaps that exist in the sterilization of tried-in SSCs and evaluates different modes of sterilization.